“Prayer for Marilyn Monroe” by Ernesto Cardenal: On the construction of a pragmatic character - Rivera Alfaro, Silvia (2026)
The poem Oración por Marilyn Monroe, byErnesto Cardenal, was written after this famous NorthAmerican actress' death. Using a prayer as a structure,the poet moves the reader to wonder about differentsocial questions. The article studies the structure, theparticipants and the different literary methods that areused for constructing this poem. Especially, it refers tothe elements that contribute to the pragmatic characterof the text and their effect on the reader.